Sources of Social Support Among International College Students in the United States - Bhochhibhoya, Amir; Dong, Yue; Branscum, Paul (Journal of International Students, 2018)
International students are challenged due to the abrupt change in social support. The purpose of this study was to operationalize different sources of social support and evaluate determinants of mental health among international students (n=328). An instrument was developed to measure four distinct sources of social support. Repeated measures ANOVA were used to evaluate statistical differences. Results found significant mean differences between each type of social support with social support from: family/friends currently living in their home country highest and friends/families living and born in the U.S. lowest. These findings provide evidence on the applicability of this new instrument. The depth in which social support is defined in this study can reflect the greater context in future research findings.